Acompañamiento pedagógico y metodológico entre la Universidad de Otavalo y CECIBs del cantón Otavalo para la enseñanza del kichwa (Segunda Fase). - Hernández, Ledys. (2021)
The project "Pedagogical and methodological support between the University of Otavalo and CECIBs of the Otavalo canton for the teaching of Kichwa", in its second phase developed during 2021 has responded to the demands and needs that have arisen in the bilingual intercultural educational units of the Otavalo canton during the health emergency caused by COVID19 that made visible the gaps and inequalities in rural community education in the online teaching modality. In this sense, the Education area of ​​the University of Otavalo responded to the emergency training of pedagogical and methodological tools of the online teaching from a first diagnosis made with teachers. I know 2 virtual teacher training workshops were carried out with a reach of 144 teachers, the participation of 38 students of the education career and the organization by of 2 responsible teachers. Finally, a closing event was held with the presentation of academic papers and dissemination of the results of the functions substantive of the area for the benefit of the Otavalo sector.